COMMUNITY SERVICE AT CEMARA LAUNDRY ON ENHANCING THE SME THROUGH MANAGEMENT THEORY AND INFORMATION TECHNOLOGY - Daris Purba; Evan Rosiska; Nanda Harry Mardika (ASOSIASI IDEBAHASA KEPRI, 2021)
The Covid-19 pandemic has decreased the revenue of Small and Medium Enterprises (SMEs), including the laundry business. Marketing efforts to increase revenue have also encountered obstacles, ranging from technical problems to cost constraints. This Community Service is aimed at a laundry in Cipta Asri Batam housing. The purpose of this Community Service activity is to foster laundry SMEs so that they can continue to exist by creating various marketing techniques and innovative products. The creation of superior and innovative products is expected to increase turnover. These superior products will be marketed using social media, given the government's health protocol. This service was organized by a team of lecturers and students from the Management and Information System Programs at the University of Putera Batam. The team from the management program coaches management and marketing, while the team from the information systems guides the field of using informatics systems in improving SME marketing and productivity. The involvement of students in this service activity is educational where students can learn directly from the field but also could provide guidance according to the knowledge that has been obtained. Coaching materials focus on marketing, business management, and the use of informatics systems. The activity was carried out in two meetings attended by the object of the event and the surrounding community. It is hoped that this service activity would be able to add insight for partners and be able to help empower partners in a better direction.